Causes of Growth in Transition Countries 1990-2012: Comparative Analysis - Mirjana Čizmović; Milenko Popović (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper provides comparative analysis of the proximate causes of growth of South East European, Central European and Former Soviet Union countries. The first section covers comparative sources of growth analysis for GDP. Apart from this conventional sources-of-growth analysis, both the demand and the industry side decomposition of the GDP growth rate, is given in second section of the paper. In the demand side of the sources-of-growth analysis, special attention is devoted to the issue of the level of capital account liberalisation and its influence on the growth anatomy. Connected with this is the issue of industry / sectors side sources-of-growth analysis. The third section covers comparative source-of-growth analysis for GDP per capita as an approximation of growth of standard of living. The results of the above mentioned different sources-of-growth approaches present a good basis for further research of fundamental causes of growth of these countries.
Keywords: O47; O52; 330; Causes of Growth; Proximate causes; Fundamental causes; Convergence